Nilai Kepemimpinan dalam Film Soekarno - Robbyansyah, Aldo; Ashrianto, Panji Dwi; Yustisia, Senja (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2021)
The background of the problem in this study discusses the case of leader who abuse their positions by doing corruption